A escola como lugar de memória: os aspectos das denominações de três escolas do município de Augusto Corrêa/PA - ALVES, Gleidson Luis Farias (2022)
The purpose of this article is to understand, using the method of oral history, the process that involves the appointment of public institutions. For the specific case presented here, I try to analyze the appointments of three public schools located in the municipality of Augusto Correa/PA, seeking to understand who are the people who lend their names to educational institutions and considering these spaces as places of memory. In this sense, I present a brief history of the foundation of the schools and a small biographical clipping of the individuals who give their names to them. The people interviewed in this research are directly linked to the aspects that led to the choice of the names of individuals to name the schools, whether due to kinship relations, politics or even just as a form of tribute.